Pendampingan Penulisan Karya Tulis Ilmiah Bagi Guru-Guru PAUD KKG Gugus Tulip Kabupaten Banjar - Ahmad Suriansyah; Erny Wahdini; Ratna Purwanti; Herti Prastitasari; Amsika Ausyra (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The teacher can communicate ideas, ideas, results from research through scientific work. Teachers who are able to write scientific papers are the main thing in developing as professional teachers, but in fact there are still many teachers who have low knowledge about writing scientific papers, this is due to the lack of teacher creativity in developing the results of activities carried out in the classroom. The purpose of the service activities carried out is to provide knowledge and writing skills of PAUD teachers of the KKG Tulip Cluster, Banjar Regency regarding the writing of scientific papers. This method of service is through lectures, questions and answers and discussions of problem analysis, as well as pre-tests and post-tests. Mentoring activities are carried out online through zoom cloud meetings. The participants were 29 PAUD teachers of the Tulip Cluster, Banjar Regency. The results of the training showed that participants were able to write scientific papers properly and precisely, at the end of the activity participants produced scientific papers.